The Relationship between Hand Washing Compliance and the Incident of Peritonitis - Rovi Agustiono; Andi Surya Kurniawan; Kurnia Laksana (PROFESSIONAL HEALTH JOURNAL, 2025)
CAPD is a dialysis method using a peritoneal membrane which is used as kidney replacement therapy. Although it is easy to implement, if it is not done correctly it can cause various complications such as peritonitis. Since the start of CAPD therapy, hand washing has been the main procedure before changing fluids. CAPD data according to IRR (2018) was confirmed from the provision of consumable medical materials or peritoneal dialysis fluid to 2,105 patients. This study aims to determine the relationship between hand washing compliance and the incidence of peritonitis in the Imam Bonjol CAPD Room, Dr. Saiful Anwar Hospital, East Java Province. This research method uses an observational analytical descriptive research design with a cross sectional method. The research sample was 177 CAPD patients using random sampling technique. The research results showed that almost all respondents had hand washing compliance in the compliant category with 147 respondents (83.1%). The research results showed that almost all respondents were in the no peritonitis category that were 153 respondents (86.4%). The results of the analysis using Fisher’s Exact Test showed that the Pvalue < α with Pvalue = 0.000 and α = 0.05, this shows that there is a relationship between hand washing compliance and the incidence of peritonitis in the Imam Bonjol CAPD Room, Dr. Saiful Anwar Hospital, East Java Province. The results show that hand washing is very important in preventing peritonitis in patients undergoing CAPD therapy. Suggestions for respondents to follow the guidelines and recommendations given by medical personnel to maintain hand hygiene, especially for CAPD patients. When possible, looking for additional information or training on hand washing practices.